Training on the Utilization of Citrus Fruits in Making Dodol to Improve the Welfare of Citrus Farmers in Lau Riman Village, Tanah Karo Regency - Warsani Purnama Sari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Citrus fruit is one of the typical Indonesian fruits that is cheap and easy to obtain, as well as one of the daily dessert fruit of the community. One of the Citrus fruit producer locations in North Sumatra is Tanah Karo Regency, where the Citrus orchards are the main livelihood of the community. Citrus Fruit itself was developed in the era of 1990 in Tanah Karo which is able to eradicate poverty and improve the education of Tanah Karo youths. Lau Riman Village, Tiga Panah Sub-district, within +/- 17 km from Kabanjahe, is a producer of Citrus orchards in besides the Merek and Munthe areas. The Citrus orchard in Lau Riman Village surrounds the village with a total of approximately eighty eight Family Heads. Siamese honey citrus or Karo itself is known as a famous sweet citrus, has a sweet smell or aroma, rough citrus flesh, rind that is easy to peel and the appearance of the fruit is quite attractive. The purpose of Community Partnership Program activities is to assist partners in improving the skills and innovation of citrus to packaging technology so that it is expected to create economic independence and increase business income. Based on observations of partners, there are several problems encountered, including: 1) There is no innovation in citrus crop yields, 2) Conventional marketing that is only awaiting the arrival of buyers, 3) Skills and limited knowledge of the utilization of citrus crops. Specific targets in the Community Partnership Program activities that result; 1) Fruit Dodol innovation 2) Marketing Strategy 4) scientific articles published in ISSN journals. The method used to achieve the Community Partnership Program activity goals is the method of education, production training, and packaging and marketing assistance. This activity was carried out for citrus fruit farmers in Lau Riman Village, Tiga Panah Sub-district, Tanah Karo Regency, which is approximately 75 km from the University of Medan Area. The choice of location is because in the village there are communities that depend on the economic life of citrus farming and there has been no innovation to citrus fruits other than just planting, harvesting, and selling fresh citrus fruits.